Dinamika Hukum Keluarga Islam Kontemporer di Indonesia: Tantangan dan Pembaruan - Rahmani, Ilham; Akbarizan, Akbarizan; Nurcahaya, Nurcahaya (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2025)
This study aims to analyze the dynamics of contemporary Islamic family law in Indonesia, with a focus on the historical evolution of the Religious Courts (PA), the Compilation of Islamic Law (KHI), and reforms such as Law Number 16 of 2019 concerning the age of marriage. The study also identifies the driving factors for social change renewal, the diversity of schools of thought, reformist thought (Muhammad Abduh, Munawir Syadzali), globalization, and human rights commitments (CEDAW, KKG), as well as challenges such as disparities in judicial decisions and textualist resistance. The research method is qualitative with a normative juridical approach and literature study, analyzing secondary data from classical/contemporary Islamic legal literature, regulations, court decisions, and fatwas of scholars through content analysis and deductive-inductive reasoning techniques. The results of the study show the evolution of Islamic family law from the ratification of the PA (Law 14/1970) to the KHI (Presidential Instruction 1/1991) and the reforms of the Reformasi era, which adopted takhayyur-talfiq for legal unification amidst the diversity of schools of thought. Reform faces obstacles such as different judges with different sentences, the failure of the Compilation of Islamic Law (CLDKHI), and conservative resistance, although breakthroughs such as raising the marriage age reflect the adaptation of the maqasid of sharia to modern issues (online unregistered marriages, digital domestic violence). Practical implications include recommendations for legislators, religious court judges, and the Religious Affairs Agency (Badilag) to harmonize sharia and human rights through maqasid-based training, community education, and contextual ijtihad to achieve gender justice and family protection.